2023
DOI: 10.3389/fmicb.2023.1333877
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the response of microbial communities to region and rootstock disease differences in tobacco soils of southwestern China

Kai Yi,
Zhenquan Li,
Deshuang Shang
et al.

Abstract: IntroductionSoil microorganisms are essential for crop growth and production as part of soil health. However, our current knowledge of microbial communities in tobacco soils and their impact factors is limited.MethodsIn this study, we compared the characterization of bacterial and fungal communities in tobacco soils and their response to regional and rootstock disease differences.Results and discussionThe results showed that the diversity and composition of bacterial and fungal communities responded more stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…The coexistence network can be used to study interactions between microorganisms, thus helping us to understand the response of microbial communities to external disturbances (de Vries et al 2018; Wang et al 2022;Wei et al 2019b;Yi et al 2023). The analysis of the coexistence network revealed that Ralstonia appeared in the CK network (purple module) and TY network (grey module) but not in the SY and TY networks.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence network can be used to study interactions between microorganisms, thus helping us to understand the response of microbial communities to external disturbances (de Vries et al 2018; Wang et al 2022;Wei et al 2019b;Yi et al 2023). The analysis of the coexistence network revealed that Ralstonia appeared in the CK network (purple module) and TY network (grey module) but not in the SY and TY networks.…”
Section: Discussionmentioning
confidence: 99%